The Corporate Management Strategies as Empowering Persons with Disabilities Through Equal Opportunity and Access to Employment in Indonesia - Emmilia Rusdiana; Arinto Nugroho; Nurnilam Sari (The Center for Disability Studies and Services Brawijaya University, 2022)
The absence of implementation instructions by formulating strategies as a model for company management as well as the company's initial provision in providing equal opportunities and preparing access to workers with disabilities. To formulate a management model as a recommendation for private companies in the policies of the district/city/provincial Manpower and Transmigration Office and agencies in the city/district government or State-Owned Enterprises companies, and as a recommendation for the preparation of academic texts of regional regulations in Indonesia. The results that the real problem is the environment or society's perspective, and companies can consider the advantages of workers with disabilities, in the form of character and abilities as well as a good image for companies. Adjustment the company's commitment to providing additional funds to prepare human resources and additional facilities to meet the needs in the work environment, increasing in the form of training on the awareness of other workers as well as awareness that persons with disabilities have rights as workers, and as business opportunities and benefits, or through company activity in the form of Corporate Social Responsibility. More recently, the synergy between companies, the government and the community of people with disabilities, in the form of imposition of rewards based on the number of permanent workers and temporary workers of people with disabilities to all companies.